Integrating tourism development projects at Gabon protected natural sites: Lessons learned from an aborted attempt - Isabelle Cloquet (Via@)
The paper addresses the reasons for the failure of an integrated conservation and development project (ICDP) which was implemented at the World Heritage site of Lopé-Okanda, in Gabon. The analysis is based on a framework provided by Blom et al.’s (2010) list of ‘best practices for ICDPs’. Key study outcomes stress the need to develop and integrate in project designs an understanding of political, sociocultural and economic conditions of the beneficiary area at the national, sub-national and local levels.